Safety assessment of the femtosecond laser in corneal limbal graft excision - O. N. Nefedova; B. E. Malyugin; S. A. Borzenok; M. Yu. Gerasimov; D. S. Ostrovsky; A. V. Shatskikh (Вестник трансплантологии и искусственных органов)
Objective: to study in vitro survival and preservation of the proliferative activity of limbal stem cells (LSCs) in femtosecond laser-cut limbal tissue fragments. Materials and methods. Limbal fragments were formed from donor cadaver eyes (n = 8) in the upper and lower limbus containing the highest number of limbal stem cells, using a Z8 femtosecond laser (FSL) (Ziemer, Switzerland). The limbal fragments were fragmented into 4 mini-grafts using different energy levels (100, 110, 120%). Mini-grafts from symmetrical sections of the cadaver eyes, which were manually isolated using a microsurgical blade, served as controls. The mini-grafts were cultured for two weeks in culture media intended for limbal epithelial stem cells (LESCs) (Epilife (0.06 mM Ca++) and for multipotent mesenchymal stem cells (MMSCs) (DMEM/F12), with the addition of specific growth factors to selectively stimulate LESCs or MMSCs, respectively. The phenotype of the obtained cultured cells in the «laser» and «knife» groups was determined by flow cytometry using a set of markers (CD166, CD105, CD90, CD29, CD34) for the membrane proteins of LESCs and MMSCs. The ability of cultured cells to adhesion and proliferation in the «laser» and «knife» groups was determined by seeding the third passage of the resulting cultures on Bowman’s membrane of acellular corneas.Results. Primary cell culture was obtained from mini-grafts of all donors in both groups. Cell morphology was consistent with the phenotype of corneal epithelial cells (cobblestone pattern). When cultured in the EpiLife medium (0.06 mM Ca++), we determined the presence of LSCs proliferation from 38.6% of minigrafts; in the DMEM/F12 medium (1 : 1) the presence was determined from 31.8%. Two weeks later, cell yield from mini-grafts in the «laser» and «knife» groups was 77.2% and 63.6%, respectively. Cell growth by the end of week 2 of culturing of mini-grafts obtained by FSL at 120, 110 and 100% energies was 87.5, 71.4 and 71.4%, respectively. It was found that the resulting cell cultures in the «laser» and «knife» groups and in the «120%», «110%» and «100%» subgroups were not different phenotypically. Cytofluorimetric analysis showed that cell cultures in the groups had a mixed pattern of marker expression of both LESCs (CD29+) and MMSCs (CD90+, CD105+). Seeding of the third passage of cell culture in the test groups in all cases demonstrated adhesion and formation of a cell monolayer on the Bowman’s membrane of model corneas.Conclusion. The use of FSL for cutting out limbal grafts seems to be effective and safe in comparison with the traditional mechanical (knife) technique. Cell cultures obtained from FSL-cut mini-grafts were able to grow and migrate for at least 21 days.